Augustine Our Contemporary : Examining the Self in Past and Present - Schreiner, Susan E. (Susan Elizabeth); Otten, Willemien (Book collections on Project MUSE., 2018)
This volume addresses Augustinian influence on the idea of the self from the Middle Ages to modernity in theology, philosophy, history, and literary studies.